IMPLEMENTASI PERATURAN MENTERI DALAM NEGERI NOMOR 2 TAHUN 2016 TENTANG KARTU IDENTITAS ANAK (KIA) DI KABUPATEN KAMPAR TAHUN 2017-2019 - Sapitri, Nadia; ", Wazni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
In order to provide a population identity to all citizens of Indonesian citizens who apply nationally, the government through the Minister of Home Affairs makes a policy, namely the Minister of Home Affairs Regulation Number 2 of 2016 concerning Child Identity Cards (KIA). Bearing in mind that children who are less than 17 years old and unmarried do not have a national identity that is valid and is integrated with the Population Administration Information System (SIAK).          The purpose of this study is to determine the implementation of Minister of Home Affairs Regulation Number 2 of 2016 concerning Child Identity Cards (KIA) in Kampar Regency 2017-2019. The theory used in this study uses the theory of the success of a policy implementation according to George C. Edward III. This type of research is descriptive qualitative. Data collection techniques are carried out by face-to-face interviews, mass media and collecting documents related to the implementation of the Minister of Home Affairs Regulation on Child Identity Cards.          The results showed that the implementation of KIA in Kampar District was not yet effective because it did not have a special printing tool to print KIA, of the 256,298 KIA required and only 556 KIA printed, this means 0.22% of the total should have been printed. Whereas based on the attachment of the Minister of Home Affairs Regulation Number 2 of 2016 concerning KIA, it is stated that the KIA blank can be personalized using the same printer and ribbon used in the Electronic KTP personalization process. Besides, it is also caused by: 1). Ineffective communication, seen from the communication channeling has not yet been carried out towards the target party, it is not clear regarding the content of the policies carried out by the implementing party, and the inconsistency in carrying out the orders contained in the policy. 2). Limited resources, inadequate information on the policy itself, ineffective implementers in exercising their authority, and inadequate facilities. 3). The attitude of policy implementers who do not know exactly what should be done and are not serious about the implementation of KIA. 4). Unrepaired bureaucratic structure. Keywords: Implementation, Children's Identity Card